1997
DOI: 10.1046/j.1469-8137.1997.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the ectomycorrhizal genus, Rhizopogon

Abstract: Seedlings oi Pseudotsuga menziesii (Mirb.) Franco, Pinus ponderosa Dougl. ex Laws, Arbutus fMeHSi' eiiV Pursh., and cuttings of Arctostaphylos uva-ursi (L.) Spreng were grown in monoculture and in conifer-hardwood dual-culture combinations in the glasshouse and inoculated with spore slurries of six Rhizopogon species. The primar\' objectives were to assess and compare the pattern of host specificity between symbionts and to study the infiuence of co-cultured plants on ectomycorrhiza development. The Rhisopogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 21 publications
(33 reference statements)
1
14
1
Order By: Relevance
“…In contrast, the number of unique Inocybe taxa in the mixed forest was four times higher than in the pure forest (8 vs. 2). The importance of neighboring plants on mycorrhizal composition was highlighted by Molina et al (1992) and experimentally A. menziesii roots in the pure forest, both of which belonged to the same Rhizopogon lineages experimentally examined by Molina et al (1997) (our present study's Rhizopogon sp. 1 = R. salebrosus and Rhizopogon sp.…”
Section: Study 2 -mentioning
confidence: 83%
“…In contrast, the number of unique Inocybe taxa in the mixed forest was four times higher than in the pure forest (8 vs. 2). The importance of neighboring plants on mycorrhizal composition was highlighted by Molina et al (1992) and experimentally A. menziesii roots in the pure forest, both of which belonged to the same Rhizopogon lineages experimentally examined by Molina et al (1997) (our present study's Rhizopogon sp. 1 = R. salebrosus and Rhizopogon sp.…”
Section: Study 2 -mentioning
confidence: 83%
“…In past studies, ectomycorrhizas have been synthesized between several Pinus species and different Rhizopogon species (see Molina & Trappe, 1994, for a complete listing) ; R. luteolus, R. roseolus and R. rubescens have received the most attention. In most of these studies, however, the morphological and anatomical descriptions of RhizopogonjPinus are general in nature, and focus on mantle colours, textures and layering, and the presence and extent of Hartig net development (Modess, 1941 ;Bjo$ rkman, 1947 ;Fontana & Centrella, 1967 ;Pachlewski & Pachlewska, 1968, 1974Froidevaux & Amiet, 1975 ;Molina & Trappe, 1982Massicotte et al, 1994 ;Molina et al, 1997). An exception is the thorough description of Rhizopogon luteolusjPinus sylvestris by Uhl (1988) and Rhizopogon subcaerulescensjTsuga heterophylla by Agerer et al (1996).…”
Section: mentioning
confidence: 99%
“…Type RWP on ponderosa pine is particularly interesting because, compared with BCl, it was dominant on ponderosa pine in all soils. In a sporeinoculation trial, Molina et al (1997) found that three Rhizopogon species (R. ellenae Smith, R. occidentalis Zeller & Dodge, and R. subcaerulescens Smith), restricted to ponderosa pine in single-host culture, were able to colonize madrone in dual culture. Further evidence of companion plant influence with respect to Rhizopogon was reported for a mixed-host assay of plantation forest soils using Douglas-fir, western hemlock (Tsuga heterophylla (Raf.)…”
Section: Discussionmentioning
confidence: 98%
“…For example, following severe fire disturbance in southwestern Oregon forest communities, ectomycorrhizal hardwoods in the genera Arbutus, Quercus, Arctostaphylos, and Lithocarpus resprout from buried rootstocks and quickly revegetate sites, thereby maintaining ectomycorrhizal fungus populations and rhizosphere processes important to development of late-seral ectomycorrhizal conifers in genera such as Pseudotsuga, Abies, and Pinus. Similar rhizosphere functions of Arctostaphylos have been suggested in other forest ecosystems (Danielson 1984;Visser 1995;Dahlberg 1990; Molina et al 1997). Perry et al (1989) hypothesize that the ectomycorrhizal hardwoods and conifers operate as a guild wherein members form with compatible mycorrhizal mutualists and participate in processes that are beneficial to the resilience and sustainability of the forest type.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation